Microbiological risk factors, ICU survival, and 1-year survival in hematological patients with pneumonia requiring invasive mechanical ventilation - Seybold, Benjamin; Funk, Timo; Dreger, Peter; Egerer, Gerlinde; Brandt, Juliane; Müller-Tidow, Carsten; Giesen, Nicola; Merle, Uta (European journal of clinical microbiology & infectious diseases, 2024)
To identify pathogenic microorganisms and microbiological risk factors causing high morbidity and mortality in immunocompromised patients requiring invasive mechanical ventilation due to pneumonia.
Gesehen am 08.01.2025